Using Social Media as a Platform for a Virtual Professional Learning Community - Laurie Bedford (Online Learning, 2019)
The Professional Learning Community (PLC) has been used in higher education to provide a platform for faculty members to discuss challenges and build professional skills. While the virtual PLC (VPLC) is becoming a more acceptable delivery mechanism for faculty professional development, successful practices for designing these learning environments has received little attention in the research literature.   Social media has been found to provide an environment in which professional learning can occur.  However, social media use for professional development has primarily focused on informal learning in unstructured formats.  The purpose of this interpretive qualitative study was to provide insight into how a purposefully structured social media platform might be used to support a VPLC.  Twenty-two doctoral mentoring faculty members from an online university agreed to participate in a VPLC using a social media platform and facilitated by expert colleagues.  Upon completion of the ten-week experience, data was collected using a self-reflective interview strategy. This study confirmed previous research into the benefits of the PLC for professional development in academia and of using social media for professional learning.  It extended the research to describe the structured, VPLC using a social medial platform to engage faculty, build relationships and foster shared learning.